The Effect of Fintech Lending on Employee Financial Health in Karawang Regency - Putra Bangie, Exelby Valen; Wanta,; Dwi Epty Hidayaty,; Arifha Mohamad, (Research in Management of Technology and Business, 2024)
With the fast-paced world, people from all walks of life, especially employees, are in dire need of proper and efficient financial management. People who would rather spend more money than they can afford. As almost all financial products today are information-based, digitalization has a huge impact on the financial services industry. The term fintech or financial technology emerged as a result of the transformation of financial services caused by advances in information technology. This study analyzes the effect of fintech lending on the financial health of employees in Karawang Regency. Fintech lending, as a digital financial service innovation, is expected to improve individual financial health. However, the results showed that fintech lending did not have a significant influence on employees' financial health. This can be seen from the calculated t value of 1.722 which is lower than the t table of 1.987, as well as a significance value of 0.088 which is greater than 0.05. Thus, there is insufficient statistical evidence to support the hypothesis that fintech lending significantly affects employees' financial health. These factors need to be considered to get a more complete picture of an employee's financial health. The implications of this study indicate the importance of developing more relevant fintech and financial education for employees to improve financial literacy and management. In addition, companies can play a more active role in supporting employees' financial health through financial well-being programs. This research also suggests that future studies explore other variables that may have more influence on financial health, such as financial literacy, income level, or money management habits.